Expert Opinion on Three Phage Therapy Related Topics: Bacterial Phage Resistance, Phage Training and Prophages in Bacterial Production Strains - Rohde, Christine; Resch, Grégory; Pirnay, Jean-Paul; Blasdel, Bob G; Debarbieux, Laurent; Gelman, Daniel; Górski, Andrzej; Hazan, Ronen; Huys, Isabelle; Kakabadze, Elene; Łobocka, Małgorzata; Maestri, Alice; et al. (Viruses, 2018)
Phage therapy is increasingly put forward as a "new" potential tool in the fight against antibiotic resistant infections. During the "Centennial Celebration of Bacteriophage Research" conference in Tbilisi, Georgia on 26-29 June 2017, an international group of phage researchers committed to elaborate an expert opinion on three contentious phage therapy related issues that are hampering clinical progress in the field of phage therapy. This paper explores and discusses bacterial phage resistance, phage training and the presence of prophages in bacterial production strains while reviewing relevant research findings and experiences. Our purpose is to inform phage therapy stakeholders such as policy makers, officials of the competent authorities for medicines, phage researchers and phage producers, and members of the pharmaceutical industry. This brief also points out potential avenues for future phage therapy research and development as it specifically addresses those overarching questions that currently call for attention whenever phages go into purification processes for application.
Keywords: potravinářská mikrobiologie; fágová terapie; Bacteria; mikrobiologie životního prostředí; lidé; Animals; Bacterial Infections; znalecký posudek; Expert Testimony; Environmental Microbiology; Food Microbiology; Phage Therapy; bakteriofágy; bakteriální infekce; zvířata; Bacteriophages; Humans